2006
DOI: 10.1097/01.ftd.0000249942.14145.ff
|View full text |Cite
|
Sign up to set email alerts
|

Teicoplanin Population Pharmacokinetic Analysis in Hospitalized Patients

Abstract: The goal of this study was to build a population pharmacokinetic (PK) model to characterize the population PK parameters in our hospitalized patients. Teicoplanin serum concentrations from clinical routine were used. Antibiotic dose history and blood collection times were recorded and analyzed with NONMEM-V. Demographic and biologic data creatinine clearance (CLcr), weight (WT), and albumin (Alb) were tested for inclusion as covariates in the basic model. Intraindividual and residual variability were modeled. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
25
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
6
25
1
1
Order By: Relevance
“…Age, body weight, creatinine clearance and serum albumin concentration can be factors that affect teicoplanin pharmacokinetic according to teicoplanin population pharmacokinetic analyses. [11][12][13] However, Pea et al reported by a multivariate analysis that the weight-adjusted dose (mg/kg), but not creatinine clearance or age, is the only significant factor that correlates with teicoplanin trough concentrations on the third day. 10) Using multiple logistic regression analysis, we also previously showed that p values were 0.046 [odds ratio (OR): 0.91, 95% confidence interval (CI): 0.82-0.99] for body weight, 0.061 (OR: 1.02, 95% CI: 0.99-1.05) for creatinine clearance and 0.592 (OR: 1.42, 95% CI: 0.39-5.3) for serum albumin concentration, indicating that only the total dose per body weight statistically significantly affected teicoplanin pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Age, body weight, creatinine clearance and serum albumin concentration can be factors that affect teicoplanin pharmacokinetic according to teicoplanin population pharmacokinetic analyses. [11][12][13] However, Pea et al reported by a multivariate analysis that the weight-adjusted dose (mg/kg), but not creatinine clearance or age, is the only significant factor that correlates with teicoplanin trough concentrations on the third day. 10) Using multiple logistic regression analysis, we also previously showed that p values were 0.046 [odds ratio (OR): 0.91, 95% confidence interval (CI): 0.82-0.99] for body weight, 0.061 (OR: 1.02, 95% CI: 0.99-1.05) for creatinine clearance and 0.592 (OR: 1.42, 95% CI: 0.39-5.3) for serum albumin concentration, indicating that only the total dose per body weight statistically significantly affected teicoplanin pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%
“…First-order conditional estimation with the interaction approach was used throughout the modelbuilding process. Teicoplanin concentration data were log transformed for analysis and were assumed to follow a two-compartment model with first-order elimination on the basis of the findings of previous studies (14,25,(32)(33)(34). The PK parameters estimated included clearance from the central compartment (CL), the central volume of distribution (V 1 ), the peripheral volume of distribution (V 2 ), and intercompartmental (central-peripheral) clearance (Q).…”
Section: Methodsmentioning
confidence: 99%
“…5, 6 Matsumoto et al suggested a target AUC 24 /MIC ratio of ࣙ900. [14][15][16][17] Therefore, an optimal loading dose is necessary to promptly achieve the target C min (>15 mg/L), 8,9,18,19 but the standard dose (400 mg of teicoplanin twice a day as a loading dose at day 1 and 400 mg once a day as the maintenance dose) is insufficient to obtain the target concentration. [8][9][10][11][12][13] Teicoplanin has a long elimination half-life (>30 hours), which leads to prolongation of the time needed to achieve a steady state.…”
mentioning
confidence: 99%
“…23 The production of CRP is promoted by inflammation associated with infection, and CRP concentrations in serum increase quickly at the beginning of infections and decrease on their alleviation. 14,15,25 However, there has been no study that has evaluated the population PKPD of teicoplanin and CRP based on data from a large-scale population. 24 A population PKPD model for predicting sequential variations of teicoplanin and CRP concentration that can be applied to a wide range of patients including the elderly, the obese, and those with renal insufficiency could provide physicians with useful information for setting individual dosing regimens.…”
mentioning
confidence: 99%